2023
DOI: 10.1590/fst.63622
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic production of selenocysteine by Enterococcus faecium ABMC-05: an indigenous lactic acid bacterium from fermented Mexican beverage

Abstract: Lactic acid bacteria have been studied for their ability to accumulate inorganic selenium, which is reduced to its elemental form or could be integrated into selenoproteins in the form of selenocysteine. This ability to produce bioavailable organic selenium for humans is an advantage that could be exploited in the production of functional foods. In this work, Enterococcus faecium ABMC-05 isolated from a traditional Mexican beverage (tepache) and with NCBI entry number OL413240 was used. Microorganism selenizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The bacterium was reported previously by our research group [21], but the identification methodology has yet to be reported. Thus, the microorganism was identified by combining MALDI mass spectrometry (matrix-assisted laser desorption/ionization), TOF (time of flight), and MALDI BioTyper software.…”
Section: Bacterium Identificationmentioning
confidence: 84%
See 4 more Smart Citations
“…The bacterium was reported previously by our research group [21], but the identification methodology has yet to be reported. Thus, the microorganism was identified by combining MALDI mass spectrometry (matrix-assisted laser desorption/ionization), TOF (time of flight), and MALDI BioTyper software.…”
Section: Bacterium Identificationmentioning
confidence: 84%
“…The experiment was carried out in separate tubes. With the viability data obtained, the MIC was determined according to the graphic method of Talmadge and Fitch reported by Escobar-Ramírez et al [21].…”
Section: Minimum Inhibitory Concentration Of Na 2 Seomentioning
confidence: 99%
See 3 more Smart Citations